Congenital anomalies among newborn babies in Felege-Hiwot Comprehensive Specialized Referral Hospital, Bahir Dar, Ethiopia - Daniel Mekonnen (Nature Portfolio, 2021)
Abstract Congenital anomaly is a structural or functional defect which could occur in any organ system. The aim of this study was to determine the prevalence and associated factors of congenital anomalies among newborn babies delivered at Felege-Hiwot Comprehensive Specialized Referral Hospital, Bahir Dar, Ethiopia. A cross-sectional study design was used to review medical records/charts of 11,177 new born babies born at the delivery ward of Felege-Hiwot Comprehensive Specialized Referral Hospital, Ethiopia. The data were collected using an abstraction form. A bivariate analysis was done to assess factors associated with congenital anomalies. Variables whose p-value < 0.2 were included in the multivariable analysis to identify the effects of confounders. P-values < 0.05 were considered statistically significant. A total of 11,177 newborn babies and their mothers were included in the study and the proportion of congenital anomalies was found to be 0.62%. The most (46.4%) prevalent congenital anomaly was neural tube defects. Newborn birth weight < 1.25 kg [AOR, 32.6, 95% CI 11.9–89.0], and newborn weight < 2.5 kg [AOR, 2.67, 95% CI 1.54–4.65], antenatal visits [AOR, 4.0, 95% CI 2.39–6.69] and urban residence [AOR, 2.1, 95% CI 1.28–3.55] were statistically significant factors. In conclusion, neural tube defects were anomalies prevalent in this study. Antenatal visits, birth weight and residence were factors associated with congenital anomalies.